2016
DOI: 10.1177/1541204016630033
|View full text |Cite
|
Sign up to set email alerts
|

Do Social Bonds Buffer the Impact of Adverse Childhood Experiences on Reoffending?

Abstract: Research from multiple disciplines has reported that exposure to childhood traumatic events, often referred to as adverse childhood experiences (ACEs), increases an individual’s chances of experiencing a wide variety of negative consequences such as chronic disease, unemployment, and involvement in serious, violent, and chronic offending. The current study assesses how protective factors from social bonds may moderate the relationship between ACEs and future offending in a sample of high-risk adjudicated youth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
75
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(84 citation statements)
references
References 49 publications
6
75
3
Order By: Relevance
“…Though prior research had indicated those with more ACEs were not only more likely to recidivate but also more likely to be serious, violent, and chronic juvenile offenders (Craig et al, 2017; Fox et al, 2015), additional evidence suggested there may be racial/ethnic and sex differences in the effects of ACEs on offending (DeLisi et al, 2017; Fagan & Novak, 2018). Further, while DeLisi and colleagues (2017) found important distinctions in the impact of ACEs on violent commitment offenses, it was unknown the extent to which this would extend to violent recidivism as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though prior research had indicated those with more ACEs were not only more likely to recidivate but also more likely to be serious, violent, and chronic juvenile offenders (Craig et al, 2017; Fox et al, 2015), additional evidence suggested there may be racial/ethnic and sex differences in the effects of ACEs on offending (DeLisi et al, 2017; Fagan & Novak, 2018). Further, while DeLisi and colleagues (2017) found important distinctions in the impact of ACEs on violent commitment offenses, it was unknown the extent to which this would extend to violent recidivism as well.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge no one has yet examined the link between ACEs and violent recidivism specifically, nor how that varies by the intersections of race/ethnicity and sex. This gap is unfortunate given the strong association between ACEs and recidivism (see Craig et al, 2017); understanding potential subgroup differences in the ACE-recidivism relationship would allow us to identify those most in need of trauma-informed treatment. The current study seeks to address this gap by examining the impact of ACE exposure on violent recidivism among a sample of confined juvenile delinquents.…”
Section: Current Studymentioning
confidence: 99%
“…Incarceration has been thought of as a time to focus interventions (Friestad et al 2014), and work to address the specific mental health and other needs of prisoners with ACEs is likely to not only benefit prison mental health but also support prisoners' rehabilitation, help build their trust in support services and have broader societal and public health benefits. Thus ACEs have been associated with recidivism in offender populations (Craig et al 2017), while levels of self-harm and suicide after release from prison are also markedly higher than rates found in the general population (Binswanger et al 2007;Borschmann et al 2016). The identification of interventions that can work to support mental health and wellbeing in prisoners affected by ACEs, and of factors that can protect against mental health difficulties in this vulnerable population, are important areas for future research.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in the United States there is extraordinary heterogeneity of background experiences among delinquents in addition to sharply divergent local life circumstances and socioeconomic backgrounds by race and ethnicity [22,23,24,25,26], which have been demonstrated to affect adverse childhood experience wherein juvenile offenders residing in more disadvantaged communities evidence greater exposures. Prior criminological research has shown that disaggregated analyses by race and ethnicity are a fruitful way to understand different pathways of offending [27,28,29].…”
Section: Introductionmentioning
confidence: 99%